2021
DOI: 10.31014/aior.1993.04.04.398
|View full text |Cite
|
Sign up to set email alerts
|

Positive Thinking Schools: Projects From Teachers

Abstract: This study was carried out within the scope of the Art of Happiness, Positive Thinking, and Subjective Well-Being Project. Within the scope of the project, 8-session pre-training was provided to teachers to inform them on the scope of positive thinking and in order to support their subjective well-being. Within the scope of positive thinking applications at schools, which formed the second stage of the project, teachers developed and applied their own projects at their schools. In the study, teachers' views on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Gür and Eser (2022) pointed out the importance of effective communication with teachers and team spirit within the scope of practices in educational environments. Effective comminucation strategies will lead meaningful task assignments which will also lead instrintic motivation (Gür et al, 2021). Onyefulu et al,(2023) suggested motivational enhancement training for administrators in order to use motivational strategies effectively for the motivation and vocational-outcome expectations of the teachers.…”
Section: Schoolsmentioning
confidence: 99%
“…Gür and Eser (2022) pointed out the importance of effective communication with teachers and team spirit within the scope of practices in educational environments. Effective comminucation strategies will lead meaningful task assignments which will also lead instrintic motivation (Gür et al, 2021). Onyefulu et al,(2023) suggested motivational enhancement training for administrators in order to use motivational strategies effectively for the motivation and vocational-outcome expectations of the teachers.…”
Section: Schoolsmentioning
confidence: 99%